Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Art news series, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Marguerite : la traversée | Épisode 2 - Transistor média
Émilie Monnet trace des parallèles entre la vie de Marguerite Duplessis et la cause des femmes, et plus particulièrement des femmes autochtones. Accompagnée de ses invité·e·s, Émilie parle de la tragédie des femmes disparues et de l’objectification dont elles sont encore victimes aujourd’hui,...
Keywords: 1700-1799; 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; arts; arts visuels et médiatiques; canada; cours; discipline; esclavage; féminisme autochtone; histoire et politique; justice sociale; martinique; performance; premier cycle; périodes historiques; québec; racisme; régions géographiques; sex2283; sexisme; système colonial; systèmes d'oppressions; thématiques; trafic sexuel; traite des femmes; violences; études littéraires